BEST PRACTICES IN UVM VERIFICATION: ENSURING ROBUST AND EFFICIENT DESIGN VALIDATION - Anil Kumar Chunduru (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2025)
This article presents a comprehensive exploration of best practices in Universal Verification Methodology (UVM) for ensuring robust and efficient design validation in complex digital systems. We begin by examining the foundational principles of UVM, including its key components such as agents, sequencers, and drivers, and emphasize the importance of modular architecture and reusability. The article then delves into practical strategies for testbench design, covering configuration databases, factory patterns, and transaction-level modeling. We provide in-depth insights into test planning, coverage-driven verification, and random stimulus generation, highlighting their crucial roles in achieving thorough validation. The article addresses common pitfalls in UVM implementation and offers effective solutions, including debugging techniques and team collaboration strategies. Advanced UVM techniques, such as assertion-based verification and formal methods integration, are explored to showcase the methodology's evolving capabilities. Finally, we examine future trends in UVM verification, including machine learning-assisted approaches and cloud-based platforms. By offering a holistic view of UVM best practices, from fundamental concepts to cutting-edge techniques, this article aims to empower verification engineers to enhance their design validation processes, reduce time-to-market, and improve overall product quality in the face of increasing system complexity.